Phytochemical Screening of Callus and Cell Suspensions Cultures of Thevetia peruviana (2018)
Thevetia peruviana is an ornamental shrub grown-up in many tropical region of the world. This plant produces secondary metabolites with biological properties of interest for the pharmaceutical industry. The objective was to determine the secondary metabolites profile of callus and cell suspension cultures of T. peruviana and compare them with those from explant (fruit pulp). Extracts in 50% aqueous ethanol and ethyl acetate were prepared. The phytochemical analysis was performed using standard chemical tests and thin layer chromatography. In addition, total phenolic and flavonoids compounds (TPC and TFC), total cardiac glycosides (TCG) and total antioxidant activity (TAA) was determined during the cell suspension growth. Phenolic chemical profile was also analyzed by high performance liquid chromatography (HPLC). Common metabolites (alkaloids, amino acids, antioxidants, cardiac glycosides, leucoanthocyanidins, flavonoids, phenols, sugars and triterpenes) were detected in all samples. The maximum production of extracellular TCG, TPC, TFC and TAA in cells suspensions were at 6-12 days; in contrast, intracellular content was relatively constant during the exponential grown phase (0 to 12-days). HPLC analysis detected one compound with retention time at 11.6 min; this compound was tentatively identified as dihydroquercetin, a flavonoid with anti-cancer properties. These results provide evidence on the utility of the in vitro cell cultures of T. peruviana for valuable pharmaceutical compounds production.